Seismic retrofit of 3000 kVA power transformer using friction dampers and prestressed tendons. (August 2021) - Naeem, Asad; Kim, Jinkoo
Abstract: This study proposes a seismic retrofit system for large power transformers with 3000 kVA capacity. The seismic protection system is developed by combining rotational friction dampers and the pre-stressed tendons with high damping rubber pads at the base. The proposed system enhances the seismic performance of the transformer by limiting the lateral and vertical deflection during earthquakes. The numerical model of the retrofit system is developed and compared with the sub-assemblage test of the damper. The seismic performance of the 3000 kVA transformer retrofitted with the proposed retrofit system is evaluated by performing full-scale shaking table test, and the results are compared with those obtained by the analytical model. The experimental and numerical results demonstrate that the seismic retrofit system is effective in reducing the deflection and acceleration of the transformer when subjected to severe ground motions.